Thoracoscopic capitonnage for pulmonary hydatid cysts: the predictors of prolonged air leak - Kakamad, Fahmi H. (Frontiers in Surgery, 2025)
ObjectivesPulmonary hydatid cysts (PHCs) represent a serious zoonotic disease that requires prompt intervention because of their potential complications. Capitonnage is one of the most common performed techniques; however, controversies surround its role in managing PHCs. The present study aims to evaluate lung parenchyma using computed tomography (CT) scans 48 h after capitonnage of PHCs performed via VATS.MethodsFifty-six patients with suspected PHCs on CT scans between 2021 and 2023 were included, while we excluded patients with risk factors for prolonged air leak (PAL), patients with other organ involvement, those presenting with emergency conditions, and those younger than 12 years old.ResultsThe CT scans revealed residual cavities in all 56 patients (100%), ranging in size from 2 to 12 cm. There was a collapse consolidation involving the affected lobe in all of the cases (100%). Eight patients (14%) experienced PAL; one patient (12.5%) had an intact cyst, while the other seven cases (87.5%) had ruptured cysts (p-value <0.001). There was no significant difference in cavity size between patients who developed PAL and those without PAL (p-value: 0.07), while patients with larger areas of consolidation tended to have PAL (p-value: 0.001).ConclusionsThe PAL is more likely caused by collapse consolidation rather than residual cavities left after the procedure. Additionally, ruptured cysts can significantly contribute to the complication of PAL.